Analisis Usahatani Wortel (Daucus carota L) Organik dan Non Organik (Studi Kasus pada Pusat Pelatihan Pertanian dan Perdesaan Swadaya (P4S) Eka Setia Lestari, Desa Bangli, Kecamatan Baturiti, Kabupaten Tabanan) - GDE NUSHA SUPUTRA; I WAYAN WIDYANTARA; IDA AYU LISTIA DEWI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2018)
The Organic and Non Organic Carrot Farming Analysis (Case Study on P4SEka Setia Lestari, Bangli Village, Baturiti Sub-District, of Tabanan Regency) The objectives of the research are to determine the differences of income of theorganic and non organic carrot farming. The second objective is to find out theconstraints faced by the organic and non organic farmers.The research wasconducted in Bangli Village, Baturiti Sub-District, Tabanan Regency. Determinationof the location is done purposively because Eka Setia Lestari already has organiccertificate and recognized by the LeSos Organic Institute. The respondents werefarmers who planted carrots during the planting season of September - December2015 at P4S Eka Setia Lestari with the number of 24 people. Determination ofrespondents of the research was conducted by census method. The analysis used wasfarm income analysis, Mann Whitney test, and descriptive analysis. The resultsshowed that the organic carrot income was Rp 7,646,446.67 and non-organic carrotincome of Rp 6,191,229.06. Based on the results of Mann Whitney test, it wasobtained significant differences between the incomes of farmers who grew organicand non-organic carrots . The constraint faced by the organic carrot farmers is thatcarrots are more susceptible to pests and diseases attacks while the constraintexperienced by the non-organic carrot farmers is the price fluctuations in the sale ofcarrots in the market.